Influence Tax Amnesty Payment of Tax Compliance SMEs Batik Moslem In District Pekalongan: (A case study of SMEs Batik Moslem in district Pekalongan 2016-2017) - Nur, Fani; Sri Khayati; Novia Zulva (International Journal of Islamic Business and Economics (IJIBEC), 2017)
This study aims to examine the effect of tax amnesty on taxpayer compliance level in paying taxes. The essence of the tax amnesty is tax forgiveness. This policy is expected to increase the willingness to pay taxes from taxpayers. This study uses primary data obtained with questionnaires for taxpayers at SMEs Batik Moslem in Dostrict Pekalongan by using random sampling systematically. This research analyzed data by using simple linear regression. The result of this research is tax amnesty have positive effect to the awareness of paying taxes, tax amnesty have positive effect to knowledge and understanding of taxpayer about taxation and tax amnesty not affect to perception about tax system effectiveness.